2020
DOI: 10.1186/s13063-020-04642-2
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, randomized, non-inferiority trial of the efficacy and safety of ciprofloxacin versus streptomycin + ciprofloxacin in the treatment of bubonic plague (IMASOY): study protocol for a randomized control trial

Abstract: Background: Bubonic plague is the primary manifestation of infection with Yersinia pestis, accounting for 90% of all plague cases and with 75% of global cases reported in Madagascar. All drugs in use for treating plague are registered based on experimental data and anecdotal evidence, and no regimen currently recommended is supported by a randomized clinical trial. The IMASOY trial intends to fill this knowledge gap by comparing two 10-day regimens included in the national guidelines in Madagascar. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Given that AMR/MDR Y. pestis strains continue to emerge in Madagascar, all but one of the 5 AMR/MDR strains identified to date in Madagascar have been resistant to streptomycin, the potential toxicity of this class of antimicrobial, and the need for it to be applied intramuscularly, streptomycin monotherapy is contraindicated and an alternative treatment regimen is warranted. To this end, a plague randomized clinical trial is ongoing for the effectiveness of ciprofloxacin monotherapy in the treatment of plague compared to streptomycin followed by ciprofloxacin [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that AMR/MDR Y. pestis strains continue to emerge in Madagascar, all but one of the 5 AMR/MDR strains identified to date in Madagascar have been resistant to streptomycin, the potential toxicity of this class of antimicrobial, and the need for it to be applied intramuscularly, streptomycin monotherapy is contraindicated and an alternative treatment regimen is warranted. To this end, a plague randomized clinical trial is ongoing for the effectiveness of ciprofloxacin monotherapy in the treatment of plague compared to streptomycin followed by ciprofloxacin [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistant Y. pestis strains may represent a threat to the exposed population if they spread in the environment and when the first-line recommended antibiotic (streptomycin) is no longer available. Fortunately, a clinical study comparing the efficiency of ciprofloxacin alone (an alternative treatment for plague) versus streptomycin-ciprofloxacin (the first-line treatment regimen for bubonic plague in Madagascar) is ongoing in multiple study sites in Madagascar ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical data indicate that many classes of antibiotics (i.e., aminoglycosides, tetracyclines, fluoroquinolones, sulfonamides, phenicols, and β-lactams) have been administered to patients with the different forms of plague [ 22 , 75 , 121 , 122 , 123 ]. A review of published case reports found that aminoglycosides, tetracyclines, and fluoroquinolones (but not sulfonamides) were most consistently effective in the treatment of pneumonic plague.…”
Section: Antimicrobial Chemotherapymentioning
confidence: 99%
“…The data did not indicate that one class of antibiotic was superior to the others. Lastly, in response to Madagascar’s 2017 plague epidemic, a randomized clinical trial of the efficacy of ciprofloxacin alone vs. streptomycin followed by ciprofloxacin is ongoing [ 122 ].…”
Section: Antimicrobial Chemotherapymentioning
confidence: 99%